SPE Annual Technical Conference and Exhibition 1992
DOI: 10.2118/24732-ms
|View full text |Cite
|
Sign up to set email alerts
|

Robust Procedures for Parameter Estimation by Automated Type-Curve Matching

Abstract: Type curve analysis of pressure transient data influenced by wellbore storage effects can yield non-unique answers due to similarity in the shapes of the curves. In order to alleviate this problem, several researchers have proposed methods for unbiased parameter estimation using nonlinear regression analysis techniques. Typically, these methods are sensitive to initial guesses for the parameter values; thus, with poor initial estimates, it is possible that the schemes may diverge or converge to wrong answers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…Commonly used procedures [3][4][5][6][7] incorporate derivative data in nonlinear regression using the incorrect objective function based on Eqs. 7 or 8.…”
Section: Mentioned Previously)mentioning
confidence: 99%
See 2 more Smart Citations
“…Commonly used procedures [3][4][5][6][7] incorporate derivative data in nonlinear regression using the incorrect objective function based on Eqs. 7 or 8.…”
Section: Mentioned Previously)mentioning
confidence: 99%
“…This rigorous theoretical result does not contradict results in the literature that suggest that the number of convergence failures or the number of iterations required for convergence may be reduced, if we regress first on derivative data to obtain initial parameter estimates and then regress on pressure. Carvalho et al 4,5 suggested that it might be best to regress first on the pressure/pressure-derivative ratio (see Onur and Reynolds 18 ) and then regress on pressure. They also suggested that outliers could be removed by applying least absolute value (LAV) regression before applying regression based on least-squares to pressure data.…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors used only the significant wavelet coefficients of permeability distribution to reduce the number of parameters, hence stabilizing the parameter-estimation algorithm. In another reparameterization application, Carvalho et al (1992) investigated the effect of using the grouped parameter set {k, k/C, Ce 2s /}, typically used in traditional type curves, instead of the primitive parameters {k, C, s}. Using the grouped parameter set did not provide any advantage over the primitive parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Many works [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] have addressed the inverse problem, involving several petrophysical parameters. The confidence of the results has been dealt with in some of them 6-12, 28, 37 .…”
Section: Introductionmentioning
confidence: 99%